Performance Evaluation of Various Algorithms for Cluster Head Selection in WSNs - Afzal , Humaira; Kanwal, Saba; Zulfiqar , M.; Gill, Humera Batool; Mufti, Muhammad Rafiq (The Nucleus, 2023)
With the huge growth of wireless sensor networks (WSNs) and massive rise in upcoming electronic devices, network management becomes difficult as it affects the overall performance of the wireless networks. Earlier, in WSN, simple clustering was employed to cover this limitation but over the time, it became evident that without an effective mechanism of the cluster formation and cluster head (CH) selection, effective WSN performance cannot be achieved. As CH selection is one of the important phases of wireless communication, that is why, it becomes essential to enhance this phase. This enhancement reflects the great improvement in the overall performance of WSNs. Different types of methodologies have been introduced in the last 10 years for cluster formation and especially for CH selection. In this article, we investigate some important methodologies such as A-LEACH, MWCSGA, DEEC-Gauss, and eeTMFO/GA of cluster formation and CH selection. From the analysis, significant results such as the energy consumption, reliability, number of alive nodes, the lifetime and throughput of network are computed that can be further utilized in selection of the best algorithm for CH selection.